Epidemiology of sport-related spinal cord injuries: A systematic review - Chan, Christie WL (J Spinal Cord Med, 2016)
CONTEXT: Despite the recognition of sports as a significant contributor in the etiology of spinal cord injury (SCI), no studies have systematically explored the epidemiology of SCI caused by sports. OBJECTIVE: This paper aims to give a systematic overview of the epidemiology of sport-related spinal cord injury around the world. METHODS: A systematic review was conducted to identify published literature reporting the epidemiology of SCI caused by sports. The literature search was conducted in MEDLINE/PubMed, CINAHL, EMBASE, PsycINFO and Sportdiscus with date limits 1980 through to July 2015. Data from 54 studies covering 25 countries was extracted and collated. RESULTS: Important findings include identification of 6 countries in which sports accounts for over 13% of SCI (highest to lowest: Russia, Fiji, New Zealand, Iceland, France and Canada); individual sports with high risk for SCI (diving, skiing, rugby, and horseback riding); and the most common level of injury for various sports (almost entirely cervical for hockey, skiing, diving and American football, while over half of horseback riding and snowboarding injuries are thoracic or lumbosacral). CONCLUSION: This paper identifies countries and sports with higher rates of sport-related SCIs where implementation of prevention programs and reporting systems to track SCI epidemiology may be helpful, and highlights gaps in our current knowledge for further investigation. The comparison of SCI occurrence for each sport across countries, as well as examination of the specific characteristics of SCI incurred for individual sports will assist in directing efforts for prevention.